Trees as islands: canopy ant species richness increases with the size of liana‐free trees in a Neotropical forest. Issue 9 (3rd October 2016) - Adams, Benjamin J.; Schnitzer, Stefan A.; Yanoviak, Stephen P.
Abstract : The physical characteristics of habitats shape local community structure; a classic example is the positive relationship between the size of insular habitats and species richness. Despite the high density and proximity of tree crowns in forests, trees are insular habitats for some taxa. Specifically, crown isolation (i.e. crown shyness) prevents the movement of small cursorial animals among trees. Here, we tested the hypothesis that the species richness of ants (Sa ) in individual, isolated trees embedded within tropical forest canopies increases with tree size. We predicted that this pattern disappears when trees are connected by lianas (woody vines) or when strong interactions among ant species determine tree occupancy. We surveyed the resident ants of 213 tree crowns in lowland tropical forest of Panama. On average, 9.2 (range = 2–20) ant species occupied a single tree crown. Average (± SE) Sa was ca 25% higher in trees with lianas (10.2 ± 0.26) than trees lacking lianas (8.0 ± 0.51). Sa increased with tree size in liana‐free trees (Sa = 10.99A 0.256 ), but not in trees with lianas. Ant species composition also differed between trees with and without lianas. Specifically, ant species with solitary foragers occurred more frequently in trees with lianas. The mosaic‐like pattern of species co‐occurrence observed in other arboreal ant communities was not found in this forest. Collectively, the results of this study indicate that lianas play an important role in shaping the local community structure of arboreal ants by overcoming the insular nature of tree crowns.